Penerapan Teknik Melempar Bola dalam Meningkatkan Motivasi dan Hasil Belajar PKn Peserta Didik SMK Negeri 1 Sakra Tahun Pelajaran 2018/2019 - Ahmad Farijan (AS-SABIQUN, 2019)
The subject of this research is the students of class X.a of SMK Negeri 1 Sakra with a total of 33 students. This type of research is a classroom action research (CAR) using quantitative and qualitative approaches. Research activities use 2 cycles. Based on the results of research analysis obtained data on student motivation in the first cycle reached 69% in the high category and in the second cycle reached 80% in the very high category. Then the evaluation results obtained in the first cycle were 9 students who were incomplete out of 33 total number of students, while the percentage of classical learning completeness achieved 70% of the results of the second cycle evaluation were 4 students who were declared incomplete out of the total 33 students , as for the percentage of mastery learning classical achieved 88%, so the research results obtained are increasing from each cycle. So the evaluation results show that the application of the Ball Throwing Technique can be well received.